Mapping of catalytically important domains in Escherichia coli leader peptidase. - Bilgin, N (1990)
Leader peptidase (Lep) is a central component of the secretory machinery of Escherichia coli, where it serves to remove signal peptides from secretory proteins. It spans the inner membrane twice with a large C-terminal domain protruding into the periplasmic space. To investigate the importance of the different structural domains for the catalytic activity, we have studied the effects of a large panel of Lep mutants on the processing of signal peptides, both in vivo and in vitro. Our data suggest that the first transmembrane and cytoplasmic regions are not directly involved in catalysis, but that the second transmembrane region and the region immediately following it may be in contact with the signal peptide and/or located spatially close to the active site of Lep.